Inhibition of metal dusting using thermal spray coatings and laser treatment - Voisey, K.T.; Liu, Z.; Stott, F.H. (Elsevier, 2006)
Alloy 600 and Alloy 800H are susceptible to metal dusting. Both alloys were thermally sprayed with two different corrosion resistant coatings: Ni50Cr and Ni31Cr11Al0.6Y. Laser remelting was used to enhance further the effectiveness of these coatings to resist metal dusting by eliminating interconnected porosity and improving coating adhesion. Uncoated, coated and laser-treated coated samples of Alloy 600 and Alloy 800H were exposed to a mixed gas atmosphere (20% H2, 80% CO at 650°C). Samples were examined in plan and cross-section using optical and scanning electron microscopy, electron probe microanalysis and X-ray diffraction. The extent of carbon deposition was tracked by mass difference measurements at intervals during exposure. The thermally sprayed coatings enhanced metal dusting resistance by acting as physical barriers to carbon ingress. The NiCrAlY coating performed well on both substrates. The NiCr coating itself underwent metal dusting and spalled from Alloy 800H due partly to CTE mis-match stresses. Laser treatment of both coatings successfully eliminated interconnected porosity and hence enhanced metal dusting resistance.